Determination of the process effect on cocoa butter crystallization by rheometer: Kinetic modeling by Gompertz equation - Boluk, Esra; Akdeniz, Esra; Gunes, Recep; Palabiyik, Ibrahim; Konar, Nevzat; Toker, Omer Said (WILEY, 2024)
In this study, the effects of temperature (22, 24, 26, 28, and 30 degrees C) and strain (0.1%, 1%, and 5%) on cocoa butter (CB) crystallization were investigated by oscillatory test, and the four-parameter Gompertz model was used to interpret the effect of parameters on pre-crystallization, nucleation, and crystal growth stages of CB. Lag time and growth rate were calculated using the Gompertz model using time-dependent storage modulus (G ') data. According to the results, CB crystallization at 26 degrees C with a 1% strain value had the highest growth rate value, the shortest lag time, and the formation of beta(v) polymorph type. Followingly, polymorphic types of the CB crystals were determined based on the melting points of polymorphs via the temperature ramp step, and the results obtained were correlated with a polarized light microscope. In conclusion, using a rheometer in both the observation of the pre-crystallization process and the determination of polymorph types is very important for research and development studies in the chocolate industry for process and formulation optimization.
Keywords: chocolate; cocoa butter; crystallization; Gompertz model; polymorph; MATHEMATICAL-MODEL; POLYMORPHISM; GROWTH; TEMPERATURE; TRANSITIONS; BEHAVIOR; SHEAR; Food Science & Technology